Analisis Faktor-faktor Risiko Infeksi Cacing Enterobius vermicularis Pada Siswa Kelas 1-2 SDN 01 Mulyorejo Kecamatan Kesesi - Ghofur, Abdul; Jeni Septia, Fina (Universitas Mohammad Husni Thamrin, 2025)
Developing countries, especially those located in tropical and subtropical regions such as Indonesia, face serious public health challenges related to helminth infections. Hookworm (Ancylostoma duodenale), Whipworm (Trichuris trichiura) and Kremi worm (Enterobius vermicularis) are the most common types of worms found in children. In Indonesia, the prevalence of worms reaches 30%-90% in some provinces, with a significant increase in infections among primary school students in rural areas. This study aimed to identify Enterobius vermicularis eggs in children in grades 1-2 at SDN 01 Mulyorejo, Kesesi sub-district, Pekalongan district and analyze the risk factors, given the lack of previous research in this location. This study is descriptive, sampling with total sampling. The sample was 21 students in grades 1 and 2 at SDN 01 Mulyorejo, Kesesi Subdistrict, Pekalongan Regency who met the inclusion criteria. Samples were examined using the selopan tape method to detect the presence of Enterobius vermicularis eggs and questionnaires and interviews to determine risk factors for Enterobius vermicularis infection. The results of the analysis of risk factors for helminthiasis showed that infected respondents did not apply good personal hygiene, such as not washing hands before eating, not cutting nails regularly, and having a habit of biting nails and sleeping together. Thus, it can be concluded that Enterobius vermicularis infection was found in grade 1 and 2 students at SDN 01 Mulyorejo, Kesesi sub-district due to lack of good hygiene. Keywords: Enterobiasis, Pinworm, Primary Student School